Efficacy and safety of early drain removal following pancreatic resections: a meta-analysis. Issue 5 (May 2023) - Chen, Kai; Liu, Zonghao; Yang, Bohan; Ma, Yongsu; Zhang, Shupeng; Shao, Zhijiang; Yang, Yinmo; Tian, Xiaodong
Abstract: Background: No consensus was reached with regard to the effect of EDR on postoperative outcomes after pancreatic surgery. The meta-analysis was designed to explore the efficacy and safety of early drain removal (EDR). Methods: Systematic literature search was performed. Data extraction and correction were performed by three researchers. For dichotomous and continuous outcomes, we calculated the pooled risk difference and mean difference with 95% confidence intervals, respectively. The heterogeneity of included studies was evaluated using Cochran's Q and I 2 test. The stratified analyses of pancreaticoduodenectomy (PD) and distal pancreatectomy (DP) were performed. Results: A total of 10 studies including 3 RCTs and 7 non RCTs were included for meta-analysis, among which 1780 patients with EDR and 5613 patients with late drain removal (LDR) were enrolled. The meta-analysis of both all the available studies and studies only with selected low risk patients indicated that EDR group had significantly lower incidences of Grade B/C postoperative pancreatic fistula (POPF) and total complications for both PD and DP. However, no advantages of EDR were observed in the meta-analysis of the 3 RCTs. In addition, EDR was associated with a lower incidence of intra-abdominal infection after PD. While for DP, EDR group had decreased risk of delayed gastric emptying and re-operation, and shorter postoperative in-hospital stay. Conclusions: The meta-analysis demonstrates that EDR is effective and safe for both PD and DP considering POPF and total complications, especially for patients with low concentration of postoperative drain fluid amylase.